Effect of chemical elicitors on the differential expression pattern of PR genes in susceptible and resistant cultivars of tomato against bacterial wilt disease caused by Ralstonia solanacearum. (December 2021) - Chaudhary, Garima; Singh, Dinesh; Sharma, Manju
Abstract: Phytopathogens induced pathogenesis-related (PR) proteins as well as defense-related signaling moleculesare imperative part of an innate immune system in plant especially for systemic acquired resistance. The present study was undertaken to find out the role of chemical elicitors on expression of pathogenicity related genes in susceptible and resistant cultivars of tomato ( Solanum lycopersicum L) against bacterial wilt and alsoon reduction of disease incidence. Two chemical elicitors i. e. Salicylic acid (SA) and β-amino butyric acid (BABA) were used in vitro, at 50, 100 and 150 μM concentrations to observe their effect on the growth of Ralstonia solanacearum (Smith) (Yabuuchi et al.1995 ). The growth of R. solanacearum was significantly inhibited by BABA and SA at 50 μM under in vitro conditions significantly. Furthermore, the relative differential expression of PR gene (PR1a, PR1b, PR2, and PR5 genes) transcripts were analyzed in both resistant (cv. Hawaii 7996) and susceptible (cv. Pusa Ruby) tomato cultivars when inoculated with R. solanacearum UTT-25 (RS)eitheralone or in combination with 50 μM concentration of BABA and SA separately at 6, 24, 48 & 96 hpi using RT-PCR. The maximum 5.61 fold up-regulation of PR1a gene was observed with SA (50 μM) +  RS while 6.44 fold upregulation of PR1b gene was noticed with SA (50 μM) alone at 48hpi in cv. Pusa Ruby. Whereas, resistant nature of cv. Hawaii7996 does not allow R. solanacearum UTT-25 to multiply, so it does not show any upregulation except with R. solanacearum alone at 96hpi of the treatment. The histochemical detection has also confirmed the minimal production of defence-related reactive oxygen species (ROS) in stems and leaves of cv. Pusa Ruby than cv. Hawaii7996 in the presence of chemical elicitors. The wilt incidences on both the cultivars at varied concentrations of the elicitors used were decreased or delayed as compared to control. In cv. Pusa Ruby with Beta-butyric acid (50 μm) +  R. solanacearum, minimum wilt incidence of 9.34 % were noticed on 16th day. However, in Hawaii7996 only 6.79 % wilt incidences were observed with Salicylic acid (50 μm) +  R. solanacearum on 24th day as compared to control. Thus, our findings suggest that chemical elicitors SA (50 μM) had inducedresistance in susceptible cultivar to reduce wilt incidence significantly under glasshouse conditions. Highlights: The growth of R. solanacearum was significantly (P < 0.05) inhibited by BABA and SA at all the concentrations (50 μM, 100 μM, 150 μM) under in vitro conditions. The pathogenesis-related genes relative expression of PR1a; PR1b and PR5 genes showed significantly (P < 0.05) 1.25–6.44 fold high level of up-regulation than other the treatments with SA and SA +  R. solanacearum, as comparative to control plants. PR1a, PR1b, and PR2 significantly (P < 0.05) showed up-regulation in Pusa Ruby whereas, down-regulation in Hawaii7996 cultivar of a tomato plant. The minimal production of defence-related reactive oxygen species (ROS) was observed in stems and leaves of Pusa Ruby than the Hawaii7996. The maximum population of R. solanacearum (6.76 log value/g of plant tissue) after 96h of inoculation and wilt incidence (63.08 %) after 28 was recorded in cv. Pusa Ruby. Minimum 9.14% wilt incidence was recorded in SA (100 μM) followed by 15.96% in BABA (50 μM) treated Hawaii7996 cultivar after 28 days of inoculation in combination with pathogen R. solanacearum.